DAMPAK PENERAPAN PSAK 10 (REVISI 2010) MENGENAI PENGARUH PERUBAHAN KURS VALUTA ASING TERHADAP DAYA INFORMATIF LABA - Arieftiara, Dianwicaksih; Yanthi, Merlyana Dwinda (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
This study aims to examine the consequences of the implementation of PSAK No. 10 (2010) regarding The Effect of Changes in Foreign Exchange Rates on the informativeness of earnings. Our research sample consists of companies listed on Indonesia Stock Exchange (IDX) from 2010 until 2013. Using panel least square linear regression, this study finds that the implementation of PSAK No. 10 (2010) improves the informativeness of earnings which is measured by Earnings Response Coefficient (ERC). This is the first study that investigates the impact of the implementation of PSAK No. 10 (2010) on ERC, therefore this study contributes on providing evidence of the impact of accounting standard revision implementation on capital market aspect.